Ocular hypertension after EyeCee One preload lens implantation: a retrospective cohort study - González-Martín-Moro, Julio; Fernández Miguel, Yolanda; Castro-Rebollo, María; Izquierdo-Rodríguez, Carlos; Prieto-Garrido, Francisco Luis; Padeira Iranzo, Victoria; Mittendrein, Vanesa; Miralles Pechuan, Vicente; Ruiz-Pomeda, Alicia; Cobo-Soriano, Rosario (Frontiers in Medicine, 2024)
Objective: In 2022 several cases of ocular hypertension (OHT) related to EyeCee One preloaded IOLs were reported. The aim of this study was to determine the presurgical and surgical variables associated with this response. Methods and analysis: An analysis was conducted on patients who underwent isolated cataract surgery between September 2022 and December 2022 at the Hospital Universitario del Henares. The influence of potential factors was studied using the Kruskal-Wallis test and multiple regression analysis. Results: 353 cataract surgeries were included in the study. No significant differences between the different IOLs were found related to a change in the IOP on the first postoperative day (p=0.395), but the change in the IOP after 1 month was higher in the EyeCee One group (p=0.016). Around 6.1% of the patients who received the EyeCee One had an IOP increase greater than 10 mmHg, compared to only 0.8% of the patients who received other IOLs. The odds ratio (OR) of experiencing an IOP increase greater than 10 mmHg in the EyeCee One group at the one-month visit was 7.99 (1.52-41.99). The multiple regression analysis showed that receiving the EyeCee One lens was associated with a 2 mmHg increase in IOP. A previous history of glaucoma or OHT was not associated with greater IOP. Two patients in the EyeCee One group developed severe visual loss. Conclusion: Patients who received the EyeCee One IOL experienced significant increases in IOP at the one¬¬ month visit. A small number of patients might suffer visual loss secondary to the rise in OP.